2017
DOI: 10.1016/s1875-5372(17)30106-6
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission Characteristics of Metal-doped Nano-diamond Cathode on Titanium Substrate

Abstract: Field emission characteristics of metal-doped nano-diamond on titanium substrate were studied, wherein metals-Ti and Hf were mixed with nano-diamond separately, and cathode samples were prepared by electrophoresis. Then the structures and morphologies of cathode samples were characterized by SEM and XRD; finally, field emission tests were conducted. Results show that the morphology of 5 mg Ti-doped sample is more uniform and dense, but the morphologies of Hf-doped samples become worse. Meanwhile, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It was found that the electronic gap state provided by the added N is beneficial to enhance the electron field emission at the surface of ND films [ 83 ]. Many attempts/changes were conducted for improving the field emission properties, such as adjusting the grain size and boundary, the concentration of sp 2 phase, and doping type/level [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Field Emission Properties Of Nd Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the electronic gap state provided by the added N is beneficial to enhance the electron field emission at the surface of ND films [ 83 ]. Many attempts/changes were conducted for improving the field emission properties, such as adjusting the grain size and boundary, the concentration of sp 2 phase, and doping type/level [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Field Emission Properties Of Nd Filmmentioning
confidence: 99%
“…Yang Y.N. group also conducted a comparative study about the effect of the Hf-doped and Ti-doped on the field emission properties of ND films, and found that the field emission characteristics of metal doped ND on Ti substrate were greatly influenced by the nature of metal Ti and Hf and the bonding reaction between nano-diamond and substrate Ti [ 93 ]. Recently, a moderate Ni-doped ND film was produced by Wang Y. et al using EPD annealing process, in which the electron-rich Ni nano-powder improved the conductivity of ND coating and effectively promotes the conversion of diamond phase into high conductive graphite phase and thus resulting in an excellent EFE properties with turn on E of 1.38 V/μm and larger maximum J of 1323 μA/cm 2 (at E = 2.94 V/μm) [ 30 ].…”
Section: Field Emission Properties Of Nd Filmmentioning
confidence: 99%